Happily [videorecording (DVD)] - Grabinski, BenDavid, 1983-; McHale, Joel, 1971-; Bishé, Kerry, 1984-; Zea, Natalie, 1975-; Scheer, Paul, 1976-; Madrigal, Al, 1971-; Morales, Natalie; Daly, Jon (Comedian); Howell-Baptiste, Kirby; Woodward, Shannon, 1984-; Yi, Charlyne; Meyer, Breckin, 1974-; et al. (Paramount Home Entertainment, 2021)
After fourteen years of marriage, Tom and Janet still can't keep their hands off each other. When they discover their friends are resentful of their constant public displays of affection, the couple starts to question the loyalty of everyone around them. Then, a visit from a mysterious stranger thrusts them into an existential crisis, leading to a dead body, a lot of questions, and a very tense couples' vacation in this dark romantic comedy.